2008
DOI: 10.5664/jcsm.27181
|View full text |Cite
|
Sign up to set email alerts
|

Does CPAP Lead to Change in BMI?

Abstract: Scientific inveStigAtionSStudy objectives: Obesity is an important risk factor for obstructive sleep apnea syndrome (OSAS), and weight loss can reduce apnea severity or even lead to resolution in some patients. Effective CPAP therapy may lead to weight loss by any of several proposed mechanisms, including, but not limited to, increased physical activity and increased responsiveness to leptin. This retrospective study sought to determine whether subjects who adhered to prescribed CPAP treatment for OSAS would l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(50 citation statements)
references
References 18 publications
3
41
1
5
Order By: Relevance
“…Weight gain after treatment with CPAP has also been documented in OSAHS [38]. CPAP treatment reduces leptin levels in OSAHS patients [39].…”
Section: Discussionmentioning
confidence: 95%
“…Weight gain after treatment with CPAP has also been documented in OSAHS [38]. CPAP treatment reduces leptin levels in OSAHS patients [39].…”
Section: Discussionmentioning
confidence: 95%
“…However, the effectiveness of CPAP in addressing OSA major risk factors, i.e., obesity, still remains unclear. Some studies found weight loss after a twelve-week CPAP therapy [28], while others highlighted that CPAP was not related to BMI change or induced body weight gain [29,30], although the latter may be due to increased lean mass as opposed to fat mass [31]. The latest American Academy of Sleep Medicine (AASM) guidelines therefore strongly recommend weight loss and lifestyle intervention combined with CPAP [22,32], which appears to be an effective treatment for moderate to severe OSA (i.e., AHI ≥ 15 events/h [22]) and is the focus of current interdisciplinary clinical and medical research [3,33].…”
Section: Introductionmentioning
confidence: 99%
“…OSA and depression are both independently related to obesity, increasing age, and adverse lifestyles, sharing common symptomatology such as daytime sleepiness, insomnia, fatigue and poor quality of life [34]. Consequently, improvement of OSA main outcome (i.e., AHI) after CPAP use may not necessarily result in a reduction in depressive symptoms due to potential remaining factors such as obesity and unhealthy habits [29]. In turn, anxiety and depression scales commonly used in order to measure baseline and posttreatment mood disturbances in patients with OSA (e.g., Hamilton Depression Rating Scale [41], Beck Depression Inventory [42], and Beck Anxiety Inventory [43]) usually include somatic symptoms found in and caused by OSA such as cardiovascular palpitations, headaches, gastrointestinal and genitourinary disturbances, loss of energy and libido, and fatigue, such that high scores of these symptoms at baseline may not necessarily signify presence of depression in patients with OSA.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, both controlled and cohort studies assessing the effect of PAP on BMI and body fat composition have reported no change after therapy (Kritikou et al, 2013;Myllyla, Kurki, Anttalainen, Saaresranta, & Laitinen, 2016;Sivam et al, 2012). Another study (Redenius, Murphy, O'Neill, Al-Hamwi, & Zallek, 2008) investigating long-term effects of PAP treatment found an increase in BMI in non-obese, but not obese, PAP users. Data from our large multicentre ESADA cohort appeared to support this notion, and further demonstrated an association between therapy compliance/duration of therapy and weight change.…”
Section: Weight Change After Pap Therapymentioning
confidence: 99%